PENGARUH METODE LATIHAN GLOBAL TERHADAP KETERAMPILAN DRIBBLING PEMAIN SEPAKBOLA KOTO MAJIDIN KABUPATEN KERINCI - EDO YULIANDRA PRATAMA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
Based on the observations of researchers in the field, it shows that the playing skills of Kotomajidin football players in Kerinci Regency are still low. This study aims to look at the effect of global training methods on ball dribbling skills. This type of research is Experimentation. The population in this study was 40 soccer players Kotomajidin in Kerinci Regency. The sampling technique was purposive sampling, namely 25 people. The data obtained is by conducting dribbling skills tests. Data were analyzed using the T test. Based on the results of research and hypothesis testing it can be concluded that there is the influence of the global training method on the ball dribbling skills of Kotomajidin football players in Kerinci Regency, it can be obtained t count> t table (9,174> 1,711). Ball dribbling skills can be seen from the average score of 5.99 in the pre test (initial test) to 4.6 in the post test (final test).